Note on Program Uncertainty in the Dynamic Programming Problem - Kao, Richard C. (Econometrica, 1962)
In this note we study the dynamic inventory problem for a follow-on provisioning in which the program length is subject to uncertainty with a known distribution. It is shown that under rather general cost conditions, the optimal policy is of the (S, s) type. This is true whether or not there exists a time lag in delivery provided that excess demand is always backlogged. The case of an infinite program horizon is also briefly discussed.